A new small frog species of the genus Pristimantis (Anura: Craugastoridae) from the northern paramos of Colombia - González-Durán, Gustavo A. (Zootaxa, 2016)
I describe a new species of a small-sized frog of the genus Pristimantis found in the paramo ecosystem (3700 masl) on the northern slope of Los Nevados National Park, Cordillera Central, department of Caldas, Colombia. This new species is assigned to the Pristimantis leptolophus species-group, given that Toe V is much longer than Toe III and extends to the distal edge of the distal subarticular tubercle on Toe IV. The new species differs from other taxa by its dorsal golden or yellowish color patterns, the absence of nuptial pads, lateral fringes on its fingers and toes, and the absence of vomerine odontophores. Discriminant analyses of morphometric characters of females of P. leptolophus, P. uranobates, and the new species separate the new species by snout-vent length, tibia length, eye diameter, eye-to-nostril distance, tympanum diameter, and length of toe III. Vomer terms frequently used to describe species are reviewed, such as the oblique keels of the vomer and the different forms of the dentigerous process. Species belonging to the high Andean Pristimantis leptolophus species-group are allopatric, suggesting vicariant speciation in different areas of the paramos.